TG4010 immunotherapy and first-line chemotherapy for advanced non-small-cell lung cancer (TIME): results from the phase 2b part of a randomised, double-blind, placebo-controlled, phase 2b/3 trial. Issue 2 (February 2016) - Quoix, Elisabeth; Lena, Hervé; Losonczy, Gyorgy; Forget, Frédéric; Chouaid, Christos; Papai, Zsolt; Gervais, Radj; Ottensmeier, Christian; Szczesna, Aleksandra; Kazarnowicz, Andrzej; Beck, Joseph T; Westeel, Virginie; et al.
Summary: Background: MUC1 is a tumour-associated antigen expressed by many solid tumours, including non-small-cell lung cancer. TG4010 is a modified vaccinia Ankara expressing MUC1 and interleukin 2. In a previous study, TG4010 combined with chemotherapy showed activity in non-small-cell lung cancer and the baseline value of CD16, CD56, CD69 triple-positive activated lymphocytes (TrPAL) was shown to be potentially predictive of TG4010 efficacy. In this phase 2b part of the phase 2b/3 TIME trial, we further assess TG4010 in combination with first-line chemotherapy and use of the TrPAL biomarker in this setting. Methods: In this phase 2b part of a randomised, double-blind, placebo-controlled, phase 2b/3 trial, we recruited previously untreated patients aged 18 years or older with stage IV non-small-cell lung cancer without a known activating EGFR mutation and with MUC1 expression in at least 50% of tumoural cells. Patients were randomly allocated (1:1) by an external service provider to subcutaneous injections of 10 8 plaque-forming units of TG4010 or placebo from the beginning of chemotherapy every week for 6 weeks and then every 3 weeks up to progression, discontinuation for any reason, or toxic effects, stratified according to baseline value of TrPAL (≤ or > the upper limit of normal [ULN]) and, in addition, a dynamic minimisation procedure was used, taking into account chemotherapy regimen, histology, addition or not of bevacizumab, performance status, and centre. Patients, site staff, monitors, the study funder, data managers, and the statistician were masked to treatment identity. The primary endpoint was progression-free survival, assessed every 6 weeks, to validate the predictive value of the TrPAL biomarker. If patients with TrPAL values of less than or equal to the ULN had a Bayesian probability of more than 95% that the true hazard ratio (HR) for progression-free survival was less than 1, and if those with TrPAL values of greater than the ULN had a probability of more than 80% that the true HR for progression-free survival was more than 1, the TrPAL biomarker would be validated. We did primary analyses in the intention-to-treat population and safety analyses in those who had received at least one dose of study drug and had at least one valid post-baseline safety assessment. Monitors, site staff, and patients are still masked to treatment assignment. This trial is registered withClinicalTrials.gov, numberNCT01383148 . Findings: Between April 10, 2012, and Sept 12, 2014, we randomly allocated 222 patients (TG4010 and chemotherapy 111 [50%]; placebo and chemotherapy 111 [50%]). In the whole population, median progression-free survival was 5·9 months (95% CI 5·4–6·7) in the TG4010 group and 5·1 months (4·2–5·9) in the placebo group (HR 0·74 [95% CI 0·55–0·98]; one-sided p=0·019). In patients with TrPAL values of less than or equal to the ULN, the HR for progression-free survival was 0·75 (0·54–1·03); the posterior probability of the HR being less than 1 was 98·4%, and thus the primary endpoint was met. In patients with TrPAL values of greater than the ULN, the HR for progression-free survival was 0·77 (0·42–1·40); the posterior probability of the HR being greater than 1 was 31·3%, and the primary endpoint was not met. We noted grade 1–2 injection-site reactions in 36 (33%) of 110 patients in the TG4010 group versus four (4%) of 107 patients in the placebo group. We noted no grade 3 or 4 nor serious adverse events deemed to be related to TG4010 only. Four (4%) patients presented grade 3 or 4 adverse events related to TG4010 and other study treatments (chemotherapy or bevacizumab) versus 11 (10%) in the placebo group. No serious adverse event was related to the combination of TG4010 with other study treatments. The most frequent severe adverse events were neutropenia (grade 3 29 [26%], grade 4 13 [12%] in the TG4010 group vs grade 3 22 [21%], grade 4 11 [10%] in the placebo group), anaemia (grade 3 12 [11%] vs grade 3 16 [15%]), and fatigue (grade 3 12 [11%], grade 5 one [1%] vs grade 3 13 [12%]; no grade 4 events). Interpretation: TG4010 plus chemotherapy seems to improve progression-free survival relative to placebo plus chemotherapy. These data support the clinical value of the TrPAL biomarker in this clinical setting; because the primary endpoint was met, the trial is to continue into the phase 3 part. Funding: Transgene, Avancées Diagnostiques pour de Nouvelles Approches Thérapeutiques (ADNA), and OSEO.